2017
DOI: 10.1038/srep40584
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor yellow A attenuates the expression of inflammatory cytokines in acute soft tissue injury

Abstract: We examined the effect of hydroxysafflor yellow A (HSYA) on the inflammatory response to strike-induced acute soft tissue injury in rats. Soft tissue injury was induced in rat leg muscles using a strike hammer, followed by intraperitoneal administration of HSYA at 16, 32, or 64 mg/kg. After 24 h, the rats were anaesthetized, blood and muscle samples were taken. Plasma levels of interleukin (IL)-6, IL-1β, and tumour necrosis factor (TNF)-αwere measured by enzyme-linked immunosorbent assay. Total RNA and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Sports-related muscle injuries in the lower extremities cause significant opportunity loss in training or competition, affecting exercise performance. The acute soft tissue injury is generally induced by external stress above a threshold, causing localized swelling, pain, bruising, blood capillary dilation, leukocyte infiltration, edema, and hemorrhage [2,3]. In this phase, neutrophils and macrophages rapidly invade injured muscle tissue and provide several important functions contributing to removal of damaged tissue, inflammation and healing [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sports-related muscle injuries in the lower extremities cause significant opportunity loss in training or competition, affecting exercise performance. The acute soft tissue injury is generally induced by external stress above a threshold, causing localized swelling, pain, bruising, blood capillary dilation, leukocyte infiltration, edema, and hemorrhage [2,3]. In this phase, neutrophils and macrophages rapidly invade injured muscle tissue and provide several important functions contributing to removal of damaged tissue, inflammation and healing [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxysafflor yellow A (HSYA), the main water-soluble ingredient extracted from Carthami flos ( Carthamus tinctorius L.), is predominantly used in the treatment of cardiovascular diseases ( Li et al, 2019 ; Xu et al, 2019 ). Previous study reported that HSYA can resist inflammation, alleviate oxidation and apoptosis, improve neurological function, alleviate infarct volume, inhibit thrombosis formation and platelet aggregation, reduce brain edema, and protect blood vessels ( Han et al, 2016 ; Wang et al, 2016 ; Dong et al, 2017 ; Sun et al, 2018 ; Li et al, 2019 ). Recently, our laboratory found that HSYA has a protective effect on hypoxia/reoxygenation-induced cardiomyocyte damage in vitro , and the mechanism was related to NLRP3 inflammasome inhibition ( Ye et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…HSYA has been demonstrated to protect cardiovascular, cerebrovascular and nerve cells, and to prevent inflammation, oxidation and tumors (30)(31)(32)(33). As aforementioned, cisplatin is one of the most commonly used cancer chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%